ANALISIS KESESUAIAN LAHAN TAMBAK KONVENSIONAL MELALUI UJI KUALITAS LAHAN DAN PRODUKSI DENGAN BANTUAN DATA PENGINDERAAN JAUH DAN SIG - Suwargana , Nana; Sudarsono, Sudarsono; Siregar, Vicentius P. (Institut Teknologi Sepuluh Nopember, 2006)
The purpose of this research are: a) To evaluate the conventional fishpond land suitability; b) To examine the land quality criteria on the conventional fishpond land suitability. The method will explore and integrate the Landsat-TM data and the Geography Information System (GIS) with parametric approach model in the study area. The result of the research and investigation are: a) The fishpond potential area for the development is estimated about 22530,5 hectare (suitable land) and is about 20966,2 hectare (suitable moderately land);b) The Land suitability criteria of the conventional fishpond in the research location are the same.